Prevalence and related factors of first-time suicide attempts in the past 14 days in Chinese adult patients with first-episode drug-naïve major depressive disorder - Cong, Xiaoyin; Zhang, Tian; Bian, Rongrong; Li, Yong; Liu, Junjun; Zhang, Xiangyang (Frontiers in Psychiatry, 2024)
BACKGROUND: This study aimed to identify socio-demographic, physiologic, and psychologic related factors of the first-time suicide attempt (FSA) in the past 14 days in Chinese adult patients with first-episode drug-naï ve (FEDN) major depressive disorder (MDD).A total of 1718 adult patients with FEDN MDD were enrolled in this cross-sectional survey. Depression, anxiety symptoms, and suicide attempts were assessed.Additionally, biological samples were collected and measured, while Logistic regression analysis was employed to explore the risk factors for FSA in the past 14 days among FEDN MDD patients.RESULTS: Among suicide attempters, 12.11% (208 out of 1718) reported experiencing FSA in the past 14 days. Logistic regression analysis showed that the risk factors for FSA included more severe anxiety symptoms (OR=1.37, 95%CI: 1.28-1.48, p<0.001), higher levels of total cholesterol (TC) (OR=1.42, 95%CI: 1.13-1.77, p=0.003), and elevated thyroid-stimulating hormone (TSH) (OR=1.13, 95%CI: 1.03-1.25, p=0.01). The regression model exhibited good discriminatory power for FSA with an area under the curve (AUC) of 0.82.FEDN MDD patients with more severe anxiety and higher levels of TSH and TC are more likely to develop FSA in the past 14 days. These factors are risk factors for short-term (in the past 14 days) FSA and may serve as indicators for early intervention.